COLORIMETRY OF TWO FLARES ON EV LACERTAE FROM UBVRI OBSERVATIONS IN 2004 - Lovkaya, M. N.; Zhilyaev, B. E. (Одеські астрономічні публікації, 2017)
According to the fast UBVRI photometry data obtained during international synchronous observations of the flaring red dwarf EV Lac, a fine time structure of two flare events is investigated and occurrence of high-frequency oscillations (HFO) during a flare is confirmed. It is revealed that HFO appear at the earliest stages of the flare development. The periods of fluctuations are from several seconds up to tens seconds. Typical amplitudes amount to some hundredths of a magnitude in the U band. HFO lead to significant variations in colors of the pure flare radiation - up to one and more magnitude. The detailed colorimetric analysis allows to note changing of such characteristics of a flare as optical thickness, electron density and temperature during the flare development. In the brightness maximum a flare radiates as a black body with temperature approximately 18500±1500 K. It is established that a flare is oscillating between the states of optically thick and optically thin in the Balmer continuum hydrogen plasma during the most part of its lifetime.